Cetacean movements in coastal waters of the southwestern Atlantic ocean - Santos, Marcos C. de O. (2019)
Cetaceans were monitored along ca. 700 km of the southeast coast of Brazil (22 degrees S to 25 degrees S) from 1995 to 2014 using photo-identification. The objective of this study was to identify any presence of long-distance movements for monitored cetacean species and discuss implications. Data on long-range movements of four of the monitored species are presented after the analysis of 321,765 photographs taken for individual identification. Seven individuals from four populations of Guiana dolphins (Sotalia guianensis) considered resident to particular estuaries or bays were reported in dispersal involving movement between pairs of protected areas over long-range distances varying between 86 and 135 km. Three cataloged rough-toothed dolphins (Steno bredanensis), first seen in Guanabara Bay, Rio de Janeiro state (22 degrees 46'S) in November 2011, were sighted 240 km southwards as members of the same group in coastal waters of Sao Paulo state (23 degrees 46'S) in July 2014. Water depth for those sightings ranged from 16 to 52.7 m; local sightings of rough-toothed dolphins in Brazil have frequently been in shallow waters, but the species global distribution is usually associated with deeper waters. In a 27-day interval in the spring of 2012, a group of 16 orcas (Orcinus orca) travelled ca. 277 km in shallow coastal waters ranging from 20 to 30 m deep. Orcas are commonly observed between November and February in southeast Brazil, probably in search for prey. In summer months between 2012 and 2014, three Bryde's whales (Balaenoptera edeni) sighted in waters ranging from 14 to 49 m deep, moved between 218 and 327 km. Bryde's whales are usually found in local coastal waters where they spend summer months feeding on sardines. To date, these are the longest estimated movements reported to S. guianensis, S. bredanensis, O. orca and B. edeni in the Southwestern Atlantic Ocean.